Intraoperative blood transfusion in pediatric patients undergoing renal transplant—Effect of renal graft size. (27th February 2018) - Odeh, Rakan I.; Sidler, Martin; Skelton, Teresa; Zu'bi, Fadi; Naoum, Naimet K.; Azzawayed, Ibraheem Abu; Alyami, Fahad A.; Lorenzo, Armando J.; Farhat, Walid A.; Koyle, Martin A.
Abstract: In pediatric RT, donor allograft size often exceeds the expected recipient norms, especially in younger recipients. An "oversize" graft might not only present a technical‐ and space‐related challenge, but may possibly lead to increased demands in perioperative volume requirements due to the disparity between donor and recipient in renal blood flow. We evaluated transfusion practices at a single tertiary institution with special consideration of kidney graft size, hypothesizing that oversize graft kidneys might lead to a quantifiable increased need of blood transfusion in smaller recipients. Retrospective analysis of all patients who underwent pediatric RT from January 2004 to June 2014 at a tertiary pediatric centre was performed. Variables analyzed included patient age, weight, pre‐ and postoperative Hb concentration, graft size, EBL, amount of intraoperative blood transfusion, and preoperative use of erythropoietin. Based on graft size in relation to patient's age, a SMR and an OvR were identified. A subcohort of age‐matched pairs was used to allow for comparison between groups. We calculated the expected procedure‐ and transfusion‐induced changes in Hb and compared these changes to the observed difference in pre‐ vs postoperative Hb to assess the influence of graft size on transfusion requirements. RT was performed in 188 pediatric recipients during the study period. In the matched cohort, percentage of transfused patients during transplantation in the OvR group was more than double compared with SMR (89% vs 39%, P < .001); similarly, the median number of transfused PRBC units in OvR was 1, while the median of SMR did not receive transfusion ( P < .001). The difference between expected (calculated) and observed change in Hb was significantly higher in OvR with a median of 1.9 g/dL compared with SMR with a median of 1.0 g/dL ( P = .026). Correspondingly, the calculated median volume taken up by a regular size kidney was significantly higher with 213 mL compared with 313 mL ( P = .031) taken up by an oversize graft kidney. Median estimated intraoperative blood loss was significantly higher in OvR than in SMR (6.9 mL/kg, vs 5.3 mL/kg, respectively; P = .04). Median postoperative Hb was similar among groups (10.4 g/dL vs 10.6 g/dL for SMR vs OvR, respectively). Transplantation of an oversized kidney in pediatric RT recipients is associated with a quantifiable higher need for blood transfusion. This may be caused by a higher intraoperative EBL and/or greater blood volume sequestered by the larger renal allograft and requires further evaluation.